2019 IEEE/CVF International Conference on Computer Vision Workshop (ICCVW) 2019
DOI: 10.1109/iccvw.2019.00127
|View full text |Cite
|
Sign up to set email alerts
|

Image Deconvolution with Deep Image and Kernel Priors

Abstract: Image deconvolution is the process of recovering convolutional degraded images, which is always a hard inverse problem because of its mathematically ill-posed property. On the success of the recently proposed deep image prior (DIP), we build an image deconvolution model with deep image and kernel priors (DIKP). DIP is a learning-free representation which uses neural net structures to express image prior information, and it showed great success in many energy-based models, e.g. denoising, super-resolution, inpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Image Deconvolution [113] Inspired by learning free deconvolution methods, modified classical UNNP's objective to deconvolution energy function.…”
Section: Compressed Sensingmentioning
confidence: 99%
See 1 more Smart Citation
“…Image Deconvolution [113] Inspired by learning free deconvolution methods, modified classical UNNP's objective to deconvolution energy function.…”
Section: Compressed Sensingmentioning
confidence: 99%
“…Wang et al [113] combined the idea of learning-free deconvolution methods with neural networks and proposed a variant of UNNP named deep image kernel prior (DIKP), in which they modified the objective function of classical UNNP to deconvolution energy function. They showed that DIKP improves the performance of image deconvolution and outperforms traditional learning-free regularizationbased priors for image deconvolution.…”
Section: Image Deconvolutionmentioning
confidence: 99%
“…Different CNN-architectures such as Scale Recurrent Network (SRN) [35], Deep-Deblur [36], MPR-Net [16] have achieved impressive performance on the task of single image deblurring without explicitly incorporating assumptions about uniform/non-uniform motion blur. There are learning based methods such as [37], [38], [39], [40] which take the forward imaging model into consideration. For example, [37] learns the Fourier coefficients of the deconvolution filter from patches of image and deconvolves the blurred image by applying the patchwise average of the predicted filter.…”
Section: Related Workmentioning
confidence: 99%
“…Wang et al [104] combined the idea of learning-free deconvolution methods with neural networks and proposed a variant of UNNP named deep image kernel prior (DIKP). They showed that DIKP improves the performance of image deconvolution and outperforms traditional learningfree regularization-based priors for image deconvolution.…”
Section: Image Deconvolutionmentioning
confidence: 99%